BENTUK MUSIK DAN FUNGSI KESENIAN JAMJANENG GRUP "SEKAR ARUM" DI DESA PANJER KABUPATEN KEBUMEN (Jurnal Seni Musik, 2017)
Jamjaneng is a music art that uses musical instrumental of kendang, gong, kempul (ukel), kemeng, thuling (kenthung) along with Islam-based religious song. The term Jamjaneng is derived from its founder, Syaikh Jamjani. This music art mostly performed as an entertainment part of wedding ceremony, khitan ceremony, slametan ocassion, and as an art program in the radio This research was aimed at finding out (1) The musical form of Jamjaneng art group â€œSekar Arumâ€ of Panjer Village in preserving its existence (2) The Functions within this Jamjaneng music art. The method of investigation was held through a descriptive-qualitative research with the analysis of data validity. The data was collected by conducting observation, interview, and document study. Technique of analyzing data of this research were data reduction, data presentation, and conclusion drawing/verification. The result of the study showed that the form of Jamjaneng music art were homophonic and polyrhythmic, the melodies were played simultaneously and had a different rhythmic pattern. According to Sudarsono, Jamjaneng music art had two functions, they were aesthetic function which shown at Jamjaneng Festival of Kebumen Regency and entertainment function which shown at wedding ceremony, khitan ceremony, and slametan occasion. Keywords: jamjaneng, Panjer, khitan, slametan